A New Divisibility Test for a Class of Integers: The Frey-Hammett Divisibility Test - Minor, Darrell (Ohio Journal of School Mathematics, 2022)
The author discusses a recently-discovered divisibility test for the infinite class of integers ending in 1, 3, 7, or 9. He explains how to apply the divisibility test, provides examples, includes an explanation (proof) of why the test works, and provides some ideas to try in the classroom. The article ends with a method for extending the divisibility test to all integers.